The Implementation of STAD in Improving Students' Reading Skill - Nurlayli Yanti; Rahil Helmi (Program Studi Pendidikan Bahasa Inggris, FKIP - Universitas Iskandar Muda, 2023)
In the process of teaching, teachers must employ various strategies to ensure that students grasp and understand the subjects they are learning. One effective strategy for teaching reading is the Student Team Achievement Division (STAD) approach. The objective of this study was to investigate the impact of the STAD technique on improving the reading comprehension scores of students at SMK Kesehatan Assyifa School in Banda Aceh. The sample for this research comprised of twenty-six second-semester grade XI students. The research involved conducting pre-tests and post-tests. The pretest was administered before implementing the STAD strategy and the posttest was conducted after four sessions of STAD treatment. The reading tests encompassed five aspects that aid in enhancing students' reading comprehension; identifying topic sentences, main ideas, details, inferences, synonyms/antonyms, and conclusions. The findings of the study revealed that students improved their reading comprehension through the STAD technique by engaging in discussions with their peers about the issues presented in the reading texts. A comparison of the pretest and posttest results demonstrated that the average score in the posttest was higher than in the pretest. Specifically, the students achieved an average score of 80.19% in the posttest, meeting the criteria for completing the minimum competency standard (KKM) set at 73%. Moreover, the students collaborated in heterogeneous teams to maximize their improvement in each cycle, which fostered a competitive atmosphere in the classroom and heightened students’ motivation to comprehend the reading texts.